Registro Brasileiro de Marcapassos: Resultados Obtidos no Primeiro Quadrimestre de 1995 - Departamento de Estimulaçao Cardíaca Artificial (Deca) - Costa, Roberto; Inês de Paula Leão, Maria (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
The Brazilian Pacemaker Registry (RBM) is a nationwide database which collects information about ali permanent pacemaker procedures performed in Brazil. It is a task force comprised of the Medicai Community, Ministry of Health and Pacemaker companies. From January 1 st - April 31 st. 1995, 2620 surgical procedures for permanent cardiac pacing were performed. There were 1911 initial implantats (74.1%) and 650 re-operations (25.2%). In 17 cases information was unavailable. Of 1911 initial implantations performed, 50.6% were males and 77.9% caucasians. Pre-operative dizziness or syncopes were refered in 80.6% and congestive heart failure in 89.2% of patients. EKG evaluation showed complete heart block in 58,6%, sick sinus syndrome in 15.8%, second degree atrioventricular block in 13.5%, and flutter or atrial fibrillation with high degree AV block in 6.9% of patients. Chagas’ disease was the predominant etiological facto r (32.5%). Ventricular pacemakers were implanted in 79.2%, and dual-chamber in 20.5% of cases; only seven patients received atrial pacing. In the 650 cases of re-operation, the interval between first surgery and the current procedure ranged from 1 month to 25 years (mean =12.6 years). Pulse generator replacements were done in 584 patients (89,9% of re-operation procedures), 82,4% of them because of battery depletion. Atriallead replacement was performed in 7, and ventricular lead replacement in 100 patients.